Developing Vocational-Based English Teaching Materials for Culinary Study Program - Husein, Rahmad; Holila Pulungan, Anni; Siregar, Masitowarni (Universitas Muhammadiyah Semarang, 2024)
Culinary is one of study programs in Vocational High School. Vocational-based English teaching materials are one of the supporting factors needed to increase students' motivation and interest in learning English. The purpose of this study was to analyze the students’ perception concerning vocational-based English teaching materials for culinary study program related to the basic competencies listed in the syllabus. The research applied qualitative method. Questionnaire consisted of 17 statements were distributed to 70 students of the second year of SMK Negeri 10 Medan. The result showed that the majority of respondents (93.19%) agreed that English teaching materials for culinary with local, national and global nuances needed to be developed. The result of two validations proved that the developed materials were eligible to be used (respectively 98.53%) of the range 81%-100%.